Efektivitas Media Articulate Storyline Terhadap Minat dan Retensi Siswa Pada Materi Biologi SMA Taman Mulia - Mauri Adisti; Mahwar Qurbaniah; Hanum Mukti Rahayu (Universitas Muhammadiyah Sorong, 2023)
Selection of the use of instructional media is necessary to create effective and innovative learning conditions that support the learning process, one of which is the articulate storyline media. This study aims to determine the effectiveness of articulate storyline media on student interest and retention. The research method used is Quasi Experimental Design with Nonequivalent Control Group Design. The treatment in the experimental class (XI IIS 2) used articulate storyline media and in the control class (XI IIS 1) used PPT. Data collection techniques using measurement techniques and questionnaires. Data collection tools used are tests and questionnaires. The results of the study show that the use of articulate storyline media is effective for students' interest and retention. The interest of the students in the experimental class differed significantly from that of the control class (independent samples t-test value of 0.000) and was influenced by the treatment by 55.4% (Effect Size value of 1.00). The retention of students in the experimental class was significantly different from the control class (U-Mann Whitney value 0.006) and was affected by the treatment by 51.6% (Effect Size value 0.92).